The Application of Digital Literacy Improves Technological Literacy in The Scope of Education in Talang Duku Village - Setyanugraha, Aldo Toto; Wahyuni, Anny (Journal International Inspire Education Technology, 2024)
Technological developments present challenges in the digital world. The demand for mastery of various devices is one of them. But not all people are able to master technology. One of the efforts of this problem is the application of digital literacy. Digital literacy must be done as early as possible, including that in children in the world of education. In this study, we conducted the application of digital literacy within the scope of education in Talang Duku village. Located at SDN 40 Talang Duku, MtsN 1 Muaro Jambi, and Man 3 Muaro Jambi with the subject of research on children of Talang Duku village in a span of two months from September 25 to November 25, 2023.  Assisting in making online flipbooks at Man 3 Muaro Jambi. Procurement of design classes and socialization on digital literacy at MtsN 1 Muaro Jambi. Featuring visualizations of educational videos to watch together at SDN 40 Talang Duku.